How do i solve equations by substitution?

Just doing one! Here’s my problem:    x-y-11  x-3y=1

So when you subsitute everything it should look like this: 1y-11-3y=1 (There needs to be a one in front of the y because it’s just always been there. they don’t always put it in the eqation. )  You need to + the 11 and you have to do that to each side. So. 1y-11-3=1
                                                                                                                +11    +11
Now it should look like this: 1y-3y=12
Combine the 1y and -3y to get -4y=12      Last step is divide -4y and 12 by 4. Answer is y=3


RELATED: